Enhancing Narrative Writing Skills through Digital Storytelling: An Experimental Study on High School Students - Atika Puspitarini; Rafiqa Rafiqa; Ahmad Junaedi (GLENS: Global English Insights Journal, 2024)
This research aims to find out the improvement of the 1st-grade students’ narrative writing by using digital storytelling and how they perceive that. The researchers used a quasi-experimental design to conduct this research. The population was 93 students and the sample elected was 15 students for both experiment and control classes. Test and questionnaire were employed to address the research questions. The data analysis was conducted using SPSS 25. The findings revealed that students’ narrative writing improved after digital storytelling was integrated into the lessons. The independent sample test showed that sig. 2 tailed < 0.05. Consequently, the alternative hypothesis was accepted, indicating a significant difference in narrative writing between students taught with digital storytelling and those taught without using digital storytelling. Moreover, the n-gain score result showed that the mean score of the experiment class was 62.09 included in the effective enough category. Therefore, it can be concluded that the use of digital storytelling is effective enough in enhancing the narrative writing of the 1st-grade students of MAN 2 Polman. Furthermore, the data from the questionnaire showed that the students had positive perceptions of using digital storytelling in classroom activities.